PENGARUH TEMPERATUR LARUTAN TERHADAP KARAKTERISTIK RAPAT ARUS-BEDA POTENSIAL MEMBRAN KITOSAN - Kusumaningtyas, Angelia Bella; Rupiasih, Ni Nyoman; Sumadiyasa, Made (BULETIN FISIKA, 2016)
The study about the characteristics of the diffusion current density-potential (J-V) of chitosan membrane has been done. It aims to determine the effect of concentration (C) and temperature (T) solution to J-V characteristic curve of the membrane. The membrane made of chitosan, as the base material (matrix) and 1% acetic acid as the solvent, with the composition of matrix/solvent of 2%. In the ion transport experiments, KCl electrolyte solution with various concentration of 0.1 mM, 1 mM, 10 mM, 100 mM, and 1000 mM and with variation of temperature of 300.9 to 340.9 K. The results showed that the value of the diffusion current density of ion sincreases with increasing the ratio of the concentration of solution in room 1 (C 1 ) and room 2 (C 2 ). The J-V curve shows non-linear relationship and it’s shifted toward larger potential with increased in temperature. These results indicate that the concentration gradient and temperature greatly affect the J-V characteristics of chitosan membrane.